(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In the context of globalization, intercultural competence has emerged as an essential element of effective English language teaching. As learners engage with English not merely as a linguistic system but as a vehicle of cross-cultural communication, teachers must adopt approaches that integrate cultural awareness and sensitivity. This article explores the theoretical foundations, pedagogical implications, and practical applications of intercultural competence in ELT, supported by empirical studies, classroom examples, and critical insights.